If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(14a + a) + -6 = 24 Combine like terms: 14a + a = 15a 2(15a) + -6 = 24 Remove parenthesis around (15a) 2 * 15a + -6 = 24 Multiply 2 * 15 30a + -6 = 24 Reorder the terms: -6 + 30a = 24 Solving -6 + 30a = 24 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 30a = 24 + 6 Combine like terms: -6 + 6 = 0 0 + 30a = 24 + 6 30a = 24 + 6 Combine like terms: 24 + 6 = 30 30a = 30 Divide each side by '30'. a = 1 Simplifying a = 1
| 32+(z+91)=91+32-51 | | 30x-7=10 | | 3x-6=10x+15 | | 8(3/8)=20t(-1/8) | | (a+6)(a+4)= | | 3/7•3 | | 12+(13+y)=25+7 | | 450000-22000x=12000x+(-155000) | | 3x-7=x+14 | | X^2+8x+8=2x | | 3x-7=x+18 | | 450000-22000x=12000x+(155000) | | ydx+(x^2-4x)dy=0 | | (-3ln+lnx)=0 | | x^3-16x-16=0 | | X^2=-12x+64 | | 7+3(x-7)=1-5(x-6) | | -7k=-6k^2 | | -60=x^2-16x | | 2j^2-4j-30=0 | | (4x+3)+57=180 | | (-2x-50)(x+17)=0 | | 3X+42=84 | | 2x=(x+13)+62 | | -1+-4r=-20 | | 1+(6+14)=(1+x)+14 | | -2y+1=y+5 | | 3(32x-256)=0 | | (x-2)(-2x+1)=0 | | 6b^2+19b+15=0 | | 3.9x-6.47=2.5 | | (2x-1)(x-12)=0 |